Impact of Metallurgical Features on the Cyclic and Torsional Properties of Five Reciprocating Instruments Manufactured With Blue Thermal Treatment - Teves Cordova, Abel Victor isidro; Alcalde, Murilo Priori; Vivan, Rodrigo Ricci; Zevallos Quiroz, Cesar Andre; Guzmán, Hubert Ponce; Calefi, Pedro Souza; Pinto, Bruna Oliveira [UNESP]; Correa, Diego Rafael Nespeque [UNESP]; Grandini, Carlos Roberto [UNESP]; Duarte, Marco Antonio Hungaro (Wiley, 2025)
This study evaluated the metallurgical and mechanical properties of five reciprocating instruments with blue thermal treatment. A total of 200 NiTi rotary instruments (25.08 and 40.06) were used: Reciproc Blue (RB), RC Blue (RCB), Only One File (OOF), Blue T (BT), and Rec Blue File (RBF). The cyclic fatigue test was performed in an artificial canal with a curvature angle of 60° and a curvature radius of 5 mm (n = 20). The time to fracture was recorded (TTF). The torsional test was performed to evaluate the maximum torsional strength and angular deflection of the instrument's tip (n = 20). Differential Scanning Calorimetry (DSC) and x-ray diffractometry (XRD) were used to assess the metallurgical features. ANOVA and Tukey tests were used for statistical comparison. The OOF 25.08 and 40.06 exhibited higher TTF than the other groups (p < 0.05). There was no significant difference among OOF, RBF, and RB 25.08 regarding the torsional strength (p > 0.05). RCB 40.06 had the lowest torsional strength (p > 0.05). DSC analysis indicated that OOF had higher austenite start and finishing temperatures. XRD analysis revealed that the 25.08 and 40.06 instruments of OOF had the highest peaks of the martensite phase. Variations in metallurgical phases and temperature transformations affected the mechanical properties of the instruments.
Keywords: cyclic fatigue; differential scanning calorimetry; nickel-titanium alloy; torsional strength; X-ray diffraction